New and emerging therapies in cutaneous T-cell lymphoma - Gabriele Roccuzzo; Nicole Macagno; Silvia Giordano; Paolo Fava; Pietro Quaglino (PAGEPress Publications, 2024)
Mycosis Fungoides (MF) is the most common cutaneous T-cell lymphoma that typically presents in the early phase as inflammatory erythematous patches or plaques, with epidermotropism as the histopathological hallmark of the disease. Traditionally, in the early stages, non-aggressive options represent the first-line strategy: topical corticosteroids, phototherapy, radiotherapy and occasionally adopting a 'wait-and-see' approach for minimally symptomatic patients. In patients with advanced or recurrence disease, good results can be achieved with immune modifiers, chemotherapeutic agents, total skin irradiation or extracorporeal photochemotherapy and maintenance therapy is often required. The past decade has seen an expansion of therapies that can be used in this setting by increasing new therapeutic strategies. Herein are resumed the key advancements coming from recently published trials.